Fertility treatment in couples with seropositivity for human immunodeficiency virus: Ethics opinion - Duru Shah; Madhuri Patil (Wolters Kluwer Medknow Publications, 2018)
Human immunodeficiency virus results in acquired immunodeficiency syndrome which alters the immune system. The virus can be transmitted through contact with infected semen, vaginal fluids, or blood.